RELEVANSI VISUAL IKLAN GOJEK CERDIKIAWAN TERHADAP TREN DAN PERILAKU GENERASI Z - ananta, Adela; Rizky Cahyani, Elliya; Pradana Wiranata, Hendra; Juliansyah, M. Verdy; Sari Yasmin, Salsabila; Fawzy, Dwimay (Universitas Muhammadiyah Jember, 2024)
This study examines the role of visual elements in Gojek’s “Cerdikiawan” digital advertisement in representing visual trends and the behavior of Generation Z. The main issue explored is how visual components can reflect current trends and connect with the behaviors of young consumers. The research aims to analyze the relevance of these visual elements using Charles Sanders Peirce’s semiotic theory, which divides signs into icons, indexes, and symbols. A descriptive qualitative method was employed, with primary data gathered through interviews with five Generation Z informants and secondary data from advertisement observations. The analysis focuses on identifying visual signs in the ad and interpreting them based on the audience’s social and cultural context. The findings show that iconic signs, such as a fork used as a creative solution, symbolize innovation and efficiency—traits valued by Generation Z. Indexical signs reflect their adaptability to technology, while symbolic elements convey emotional messages that enhance Gojek’s brand image. This study offers insights into how visual advertising can emotionally engage younger audiences through semiotic interpretation.